Hypovolemia-related gastric tissue damage in the setting of upper gastrointestinal bleeding - Melih KARINCAOGLU; Yüksel SEÇKİN and Fehmi ATEŞ and Murat MM HARPUTLUOĞLU and Kadir BATÇIOĞLU and İrem Pembegül YİĞİT and; lyas ÖNER and Fatih HİLMİOĞLU (Turkish Journal of Gastroenterology, 2019)
-